Pemberdayaan masyarakat dalam pengolahan air Sungai Batanghari menjadi air bersih menggunakan adsorben biochar - Nelson Nelson; Helga Dwi Fahyuan; Frastica Deswardani; Nurhidayah Nurhidayah; M Ficky Afrianto (Riau Journal of Empowerment, 2020)
Sungai Duren is one of the villages that has concern of the local government for the provision of clean water because of the difficulty in accessing clean water in the village. The resident do not yet have access for clean water, and still very dependent on Batanghari river water. While the turbidity and water quality of Batanghari river does not have clean water requirements. Based on that facts it is necessary to provide assistance through counseling and demonstration about simple technology to treat and purify Batanghari river water into drinking water by tools and materials that easily obtained and made. Water filtration technology was easily to made and then biochar material can be used as an absorbent. Biochar does not experience further weathering so it would take a long time when it applied as a water filter. The source of biochar was from oil palm empty fruit bunches that not utilized. Some steps that need to be taken so the solution can be realized are first by providing counseling by socialization of the importance of the availability of clean water for community and the use of biochar as an adsorbent for water filtration.